Megaviruses contain various genes encoding for eukaryotic vesicle trafficking factors. (28th June 2022) - Khalifeh, Dany; Neveu, Emilie; Fasshauer, Dirk
Abstract: Many intracellular pathogens, such as bacteria and large viruses, enter eukaryotic cells via phagocytosis, then replicate and proliferate inside the host. To avoid degradation in the phagosomes, they have developed strategies to modify vesicle trafficking. Although several strategies of bacteria have been characterized, it is not clear whether viruses also interfere with the vesicle trafficking of the host. Recently, we came across SNARE proteins encoded in the genomes of several bacteria of the order Legionellales. These pathogenic bacteria may use SNAREs to interfere with vesicle trafficking, since SNARE proteins are the core machinery for vesicle fusion during transport. They assemble into membrane‐bridging SNARE complexes that bring membranes together. We now have also discovered SNARE proteins in the genomes of diverse giant viruses. Our biochemical experiments showed that these proteins are able to form SNARE complexes. We also found other key trafficking factors that work together with SNAREs such as NSF, SM, and Rab proteins encoded in the genomes of giant viruses, suggesting that viruses can make use of a large genetic repertoire of trafficking factors. Most giant viruses possess different collections, suggesting that these factors entered the viral genome multiple times. In the future, the molecular role of these factors during viral infection need to be studied. Abstract : Giant viruses enter their eukaryotic host cells by phagocytosis. For reproduction, they hijack the host cell's membranes by an unknown mechanism. Here, we found that giant viruses express several core factors of the eukaryotic vesicle fusion machinery, including SNARE, Rab, SM proteins, and the disassembly protein NSF. Very probably, these genes were transferred from different eukaryotic hosts to different viruses. Whether the viruses deploy these factors for interfering with the vesicle trafficking of the host cell needs to be investigated.